RANCANGAN SISTEM INFORMASI PERSEDIAAN STOK OBAT DENGAN METODE SYSTEM DEVELOPMENT LIFE CYCLE DI APOTEK NUSA FARMA NUSA PENIDA - Ramayu, I Made Satrya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The pharmacy data processing system is still managed traditionally, especially in the Nusa Penida area. The ledger records every transaction and piece of data. This is very inefficient because generating reports takes a lot of time and introduces a lot of errors, and negative things can happen if data is lost or corrupted. The scope of this research question is to design a pharmacy information system with the aim of facilitating data processing to provide more accurate and timely information in accordance with the expectations and needs of users in order to increase efficiency, improve work efficiency, and improve pharmacy services to customers. The system is designed to enable administrators to create transaction records, inventory reports, and other items in the pharmacy. In this study, the SDLC (System Development Life Cycle) methodology was used, and the system was made web-based using the MySQL database. Black box testing is used in this study. This pharmacy system architecture can process user data, account data, income transaction data, expenditure transaction data, and stock cards that can see expired and expired drugs and generate stock inventory reports.